The prevalence of gastrointestinal parasites of turkeys (meleagris yallopavo) - Ferda Sevinç; Feyzullah Güçlü; Mehmet Yaman; Funda Altınöz (Eurasian Journal of Veterinary Sciences)
This study was carried out on domestic turkeys in Central villages of Konya between August 1996-December 1999. Macroscopic examination of whole gastrointestinal system oi 40 turkeys and microscopic examination ol the fecal samples of 450 turkeys were performed. Various parasite species were determined in 52.5 % of turkeys. Eımena sp., Heterakis gallinarum. Subulura differens, Echinostoma revolutum, Ascaridia galli were respectively detected at the rate of 37.5 %, 15 %, 7.5 %, 5 %, 2.5 %, in the macroscopic examination ol gastrointestinal system. The fecal samples were examined by the Fulleborne's salt saturated flotation and Benedek sedimentation methods, and in 111 (24.66 %) ol tecal samples were found to be parasitised. Eimeria sp. oocysts. Capıllarıa sp., As-candia sp., Choanotaenia mfundibulum, Trichostrongylus tenuis and Heterakis gallinarum eggs were respectively detected at the rate of 12.88 %, 7,11 %, 6.44 %, 1.55 %, 1.33 %. 0,08 %in the microscopic examination of lecal samples.